2015
DOI: 10.1515/chempap-2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical sensor for sensitive determination of nitrites based on Ag–Fe3O4–graphene oxide magnetic nanocomposites

Abstract: A functional Ag-Fe3O4-grapheme oxide magnetic nanocomposite was synthesized and used to prepare a nitrite sensor. Morphology and composition of the nanocomposites were characterized by a transmission electron microscope, UV-VIS spectroscopy, X-ray diffraction, and Fourier transform infrared spectra. Electrochemical investigation indicated that the nanocomposites possess excellent electrochemical oxidation ability towards nitrites. The sensor exhibited two linear ranges: one from 0.5 µM to 0.72 mM with a correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The detection limit of nitrite is 0.24 µM and the detection range is from 1 µM to 1000 µM. [76]. This material modified GCE was used to detect nitrite.…”
Section: Metalsmentioning
confidence: 99%
“…The detection limit of nitrite is 0.24 µM and the detection range is from 1 µM to 1000 µM. [76]. This material modified GCE was used to detect nitrite.…”
Section: Metalsmentioning
confidence: 99%
“…Real samples for Nitrite [52] Alternatively, magnetic nanoparticles could bind with graphene or its derivatives via covalent coupling reaction including amidation reaction and click chemistry [22][23][24][25][26][27][28][29][30][31]. For example, Bi et al reported magnetic GO-hemin composites probes based on amidation reaction [22].…”
Section: Non-covalent Assembly Methodsmentioning
confidence: 99%
“…Urea was detected with a concentration range of 5–100 mg/dL and with limit of detection was 0.5 mg/dL [ 44 ]. In year 2015, Li et al developed a nitrite sensor by using the Ag–Fe 3 O 4 –graphene oxide magnetic nanocomposite, with a linear range of 0.5 μM–0.72 mM and the lower limit of detection was 0.17 μM [ 45 ]. In 2016, Lee et al used Fe 2 O 3 /graphene NPs for fabricating electrochemical sensor for detecting Zn 2+ , Cd 2+ and Pb 2+ metal ions.…”
Section: Advancement Of Nanotechnology and Nps-based Biosensorsmentioning
confidence: 99%